Analysis of Concept Map about ICT Education of Early Childhood Teachers - Man Kim, Byung; Young Jung, Hye (International Journal of Engineering and Technology, 2018)
Background/Objectives: The purpose of this study was to use a concept map analysis about ICT education for early childhood teachers and tries to look into knowledge and structure about ICT education. Methods/Statistical analysis: The subject of this study was randomly collected 50 early childhood teachers working in kindergartens located in Busan, Gyeongsangnam province. The conceptual diagrams drawn up by the early childhood teachers were analyzed to find out the numbers of superordinate concepts, the number of content elements, characteristics, hierarchy and density. Findings: First, as for the content of education for happiness, superordinate concepts appeared 354 times in the conceptual diagrams of the early childhood teachers, and there were 21 superordinate concepts overall in their diagrams. Second, early childhood teachers had more knowledge of ’computer education’ of ICT education. Third, density of individual concept map of early childhood teachers appears in range from 1.00 to 8.60, and average density appeared 3.34. In addition, since average of group about density appeared higher than average of subordinate group and there was significant difference statistically, difference among individual teachers were appeared big in density of concept. Improvements/Applications: This study suggests possibility and direction about ICT education by executing analysis of concept map about ICT education for early childhood teachers, and has meaning about providing practical material about possibility of ICT education. Â